Infants Nutrition: Supplementary Feeding of Breastfeeding Infants Variation - Rifa Rahmi; Rika Ruspita (Science Midwifery, 2021)
Supplementary Feeding of Breastfeeding are foods or drinks that contain nutrients, given to infants or children aged 6-24 months to meet nutritional needs other than breastfeeding. In an emergency, infants and toddlers should receive complementary foods to prevent malnutrition. Variety of food ingredients for babies is important because no single food is sufficient for the needs of babies. A variety of complementary foods to breast milk can help meet the nutritional needs of the baby. The research objective was to determine the prevalence of nutrition and variations in complementary foods as well as the relationship between variations in complementary foods and the fulfillment of infant nutrition in Tenayan Raya District, Pekanbaru. This research method uses quantitative observational analytic research with cross-sectional analytic study design. The study population was all infants aged 6-12 months in the District of Tenayan Raya with the sampling technique using consecutive sampling totaling 30 samples. Data analysis was performed univariate and bivariate using SPSS. Based on the results of the research that has been done, it can be concluded (1) the mean of infant nutrition is z score -0.203; (2) The average variation of MP ASI is 7 variations; (3) There is a correlation of variations in complementary feeding to the nutritional fulfillment of aged infants in the District of Tenayan Raya Pekanbaru.